Effect of Vitamin C and E Supplementation on Stress Response Banggai Cardinalfish (Pterapogon kauderni) - Sari, Devi Elvina; Mubarak, Ahmad Shofy; Sulmartiwi, Laksmi (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the effect of giving a combination of vitamins C and E as Artemia sp. supplementation on the level of stress resistance of Banggai cardinalfish. The research method used a completely randomized design. The treatments used were a combination of vitamins C and E in supplementation of Artemia sp. as feed: A (vitamin C 57.50 mg/L + vitamin E 28.75 mg/L), B (vitamin C 115 mg/L + vitamin E 57.50 mg/L), C (vitamin C 230 mg/L + vitamin E 115 mg/L), D (vitamin C 460 mg/L + vitamin E 230 mg/L), and E (vitamin C 920 mg/L + vitamin E 460 mg/L), each treatment was repeated 4 times. The main parameters observed were the level of stress resistance (frequency of pectoral fin movement, frequency of operculum movement, frequency of mouth movement) and blood glucose. Data were analyzed using analysis of variance (ANOVA) and further tests were carried out to determine the differences between treatments. The results showed that supplementation of vitamin C and E in Artemia sp. with different dose combinations had a significant effect (P < 0.05) on the frequency of pectoral fin movements, operculum movement frequency, and mouth movement frequency after hypoxia treatment at the 2nd, 4th and 8th hours and blood glucose levels after hypoxia treatment. The best stress resistance level during the study was in treatment C (vitamin C 230 mg/L + vitamin E 115 mg/L), while the lowest was in treatment A (vitamin C 57.50 mg/L + vitamin E 28 mg/L).